STRATEGI PENGELOLAAN KELAS UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Utin Emma Dafiana Erta (Jurnal AlphaEuclidEdu, 2022)
This study aims to improve student learning outcomes with strategies to increase student confidence in class IX A of SMP Negeri 2 Sanggau. This research was carried out in the second semester of the 2021/2022 academic year with learning activities carried out in two sessions, face-to-face meetings (PTM) and learning from home (BDR). The research conducted was classroom action research which consisted of two cycles, and each cycle consisted of two meetings. Each research cycle consists of four stages, namely: planning, action, observation, and reflection. The results showed that with increasing students' self-confidence, the learning outcomes obtained by students also increased as seen from the learning outcomes obtained by students in the first cycle by 75.00% to 87.50% in the second cycle.